Antibacterial Properties of Nanosized Silver Colloidal Solution on Wool Fabric - Maleknia, Laleh; Asghar Aala, Ali; Yousefi, Kia (Asian Journal of Chemistry, 2010)
This paper deals with the antibacterial efficacy of nanosized silver colloidal solution on the wool fabrics. Two kinds of bacteria Staphylococcus aureus and Escherichia coli were used. The morphologies, structures and antibacterial properties were characterized by using transmission electron microscopy (TEM), scanning electron microscopy (SEM), EDAX and AATCC-100 test method. Transmission electron microscopy observation of silver nano particles showed the particles were very small (6-8 nm). Scanning electron micrographs of treated fabrics indicated silver nano particles were well dispersed on the surfaces of samples. EDAX patterns showed that the per cent of nanosized silver particles increased on the surface of samples with increase concentration of colloid solutions nano silver. The results prepared of antibacterial test method indicated excellent antibacterial effect on all specimens against S. aureus and E. coli.